Conceptualizing Entrepreneurial Education as a Social Justice Endeavor - Sarah M Ray; Jill Zarestky; Lisa Baumgartner (Adult Education Research Conference, 2018)
Entrepreneurial education is typically capitalist and overlooks social change efforts. Grounded in the literature, we argue progressive adult education has potential to transform entrepreneurial education into a social justice endeavor.
Keywords: Social justice; entrepreneurial; adult education